IMPLEMENTASI VISI, MISI DAN PROGRAM RAUDHATUL ATHFAL AL-BAROKAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH - Kartika Hanifah; Abd Rozak; Hilmi Luthfiyah (Irfani, 2025)
This study aims to describe the implementation of the vision, mission, and work program in improving the quality of learning at RA Al-Barokah, Bogor Regency. The approach used is descriptive qualitative with interview techniques and documentation studies. The results of the study indicate that the institution's vision and mission are implemented through learning programs, teacher and education staff development, and supporting programs such as extracurricular activities, parenting, and infrastructure. This implementation has a positive impact on improving the quality of the learning process, teacher competency, and student development according to RA national standards. Success is supported by the leadership of the RA head, foundation support, and parental involvement, although there are still obstacles such as limited resources and regulatory changes. The strategy implemented at RA Al-Barokah has the potential to become a model for quality improvement for other RA institutions, provided there is commitment and cooperation between parties.